Asuhan Kebidanan Komprehensif pada Ny.N dengan Faktor Resiko Umur >35 Tahun dan Multiparitas di Puskesmas Paguyangan Kabupaten Brebes - Intan Tri Lestari; Endang Susilowati; Widi Astuti (Nursing Applied Journal, 2025)
This study aims to provide an overview of comprehensive midwifery care in reducing maternal morbidity and mortality at the Paguyangan Health Center, Brebes Regency. According to WHO data in 2023, the maternal mortality rate was recorded at 4,129 per 100,000 live births, with the same rate in Indonesia and 335 per 100,000 in Central Java. In Brebes Regency, there were 54 cases of maternal death caused by various factors. This study used a case study method with a descriptive approach to analyze midwifery care during pregnancy, childbirth, postpartum, newborn care, and family planning programs. The results show that Mrs. Ny. N, aged 35 and with a history of multiparity, had a pregnancy with high-risk factors. Despite this, her delivery proceeded naturally with a spontaneous birth of a female baby, who cried loudly, weighing 3110 grams, and measuring 50 cm in length. During the postpartum period, no complications were found, uterine reflexes were normal, and lochia was physiologically appropriate. The baby was healthy and received hepatitis B immunization and vitamin K1. In the family planning program, the mother chose to use a 3-month injection contraception. The conclusion of this study is that despite the high-risk factors faced by the mother, comprehensive midwifery care can help minimize risks and improve the quality of care during pregnancy and childbirth.